A Rare Manifestation of Metastatic Breast Cancer: Cervical Esophageal Stenosis with Oropharyngeal Dysphagia Decades After Primary Treatment - Made Gede Krisna Rendra Kawisana; I Wayan Sucipta; I Putu Santhi Dewantara (Open Access Indonesian Journal of Medical Reviews, 2025)
Esophageal metastasis from breast cancer is an infrequent occurrence, with cervical esophageal involvement being exceptionally rare. Presentation with oropharyngeal dysphagia, particularly decades after primary breast cancer treatment, poses a significant diagnostic challenge. This report details such a case, emphasizing the clinical course and diagnostic complexities. A 60-year-old female, with a history of primary breast cancer treated approximately two decades prior and subsequent treatment for a locoregional recurrence with surgery, chemotherapy, and radiotherapy in 2019, presented with progressive oropharyngeal dysphagia and aspiration over three months. Initial Fiberoptic Endoscopic Evaluation of Swallowing (FEES) suggested upper esophageal pathology with stenosis and extraluminal mass compression at the introitus esophagus. Esophagoscopy confirmed a high cervical esophageal stenosis impassable with the scope. Computed Tomography (CT) of the neck revealed a large heterogeneous solid mass at the C6-Th2 level, encasing the trachea and causing severe cervical esophageal stenosis with suspected wall infiltration, along with widespread metastatic disease including pulmonary and osseous metastases. In conclusion, this case highlights the critical importance of maintaining a high index of suspicion for metastatic breast cancer in patients presenting with new-onset oropharyngeal or esophageal dysphagia, even many years after their initial cancer diagnosis and treatment. Cervical esophageal metastasis, though rare, should be considered in the differential diagnosis. A multidisciplinary approach and comprehensive diagnostic evaluation, including advanced imaging, are paramount for accurate diagnosis and guiding appropriate palliative management.